E-Litigation in Algeria - Cherroun, Hacina (Revue jurisprudence; Vol. 11 No 02 (2019): مجلة الاجتهاد القضائي, 2019)
The subject of litigation over the Internet, witch called electronic litigation, as a mechanism adopted by most countries in the justice sector, because of its advantages in the conduct of public proceedings, such as reducing the burden on the parties to the public lawsuit, lawyers, judges, etc., In light of the important and distinct position occupied by the justice sector and its attempt to keep abreast of developments and technological changes by adopting the electronic litigation system, the problem of this study is reflected in the following main question: What are the effective means required by the system in order to achieve the goals of the judiciary? What is the reality of electronic litigation mechanism in Algeria? Through this intervention, we aim to reveal the mechanism of litigation through the Internet, to know its concept, its characteristics, and to indicate the means that must be met in order for the justice sector to achieve the established objectives, to present its application on the ground, Algeria as a model. In order to answer the problem and the secondary questions, we followed the descriptive and analytical approach, in order to control the various concepts related to the electronic litigation mechanism. We divided this study into three axes as follows: The first axis: the concept of electronic litigation. The second axis: the means of electronic litigation. Third: The application of electronic litigation mechanism in Algeria.